Losing, using, refusing, cruising : first-generation South African women academics narrate the complexity of marginality - Idahosa, Grace Ese-Osa (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
While existing literature shows a considerable increase in the numbers of women in academia research on the experiences of women in universities has noted their continued occupation of lower status academic positions in relation to their male counterparts. As the ladder gets higher, the number of women seems to drop. These studies indicate the marginalization of women in academic settings, highlighting the various forms of subtle and overt discrimination and exclusion women face in academic work environments. In this study I ask how academic women in South Africa narrate their experience of being 'outside in' the teaching machine. It has been argued that intertwined sexist, patriarchal and phallocentric knowledges and practices in academic institutions produce various forms of discrimination, inequality, oppression and marginalization. Academic women report feeling invisible and retreating to the margins so as to avoid victimization and discrimination. Others have pointed to the tension between the 'tenure clock' and the 'biological clock' as a source of anxiety among academic women. Where a masculinised presentation of the self is adopted as a solution to this dilemma, the devaluation of the feminine in the academic space is confirmed. However, experiences of academic women are not identical. In the context of studies showing the importance of existing personal and social resources, prior experience and having mentors and role models in the negotiation of inequality and discrimination, I document the narratives of women academics who are the first in their families to graduate with a university degree. These first-generation academic women are therefore least likely to have access to social and cultural resources and prior experiences that can render the academic space more hospitable for the marginalised. Employing Spivak's deconstruction of the concept of marginalisation as my primary interpretive lens, I explore the way in which, in their narratives, first-generation academic women negotiate marginality. These narratives depict a marginality that might be described, following Spivak, as 'outside/in', that is, as complex and involving moments of accommodation and resistance, losses and gains, pain and pride.
Keywords: Women in higher education -- Research -- South Africa; Women college teachers -- Research -- South Africa; Sex discrimination in higher education -- Research -- South Africa; Feminism and higher education -- South Africa; Marginality, Social -- South Africa